Frequency of Complications in Admitted Patients of Diabetic Ketoacidosis - Irfan Ali Jhatial, Muhammad Ashfaq, Mehrunnisa Yasir, Yasir Naqi Khan, Bader-u-Nisa, Shabeeta Bai, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of different complications in admitted patients of diabetic ketoacidosis (DKA). Study Design: A cross-sectional study. Place and Duration: Diabetic ward of National Institute of Child Health (NICH), Karachi Pakistan from 1st November 2020 to 31st October 2021. Methodology: A total of 253 children of either gender aged 1 to 15 years admitting with DKA and duration of diabetes mellitus ≥3 years were included. All patients were subjected to detailed history and clinical examination for DKA and its complication like hypoglycaemia, hypokalaemia, hyponatraemia, hypocalemia, hyperkalaemia. Resutls: In a total of 253 children admitted with DKA, 123 (48.6%) were girls and 130 (51.4%) boys. Mean age of patients was 6.11 ± 2.87 years, mean BMI was 20.9± 4.7 kg/m2, while mean duration of diabetes mellitus was 3.5± 1.2 years. Mean plasma glucose was 22.5±6.0 mmol/L (405±108mg/dl), mean HbA1c 10.2±2.1% while mean pH was 6.9±0.4. In a total of 253 patients with DKA, hypoglycemia was noted in 47(18.6%), hypokalemia 17 (6.7%), hyponatremia 22 (8.7%), hypocalcaemia 11 (4.35%) while hyperkalaemia was observed in 9 (3.56%) patients. Conclusion: Most of the patients admitted with DKA were aged <10 years who developed complications. Hypoglycemia was the most common complication of DKA while hyponatremia the 2nd most frequent complication observed in DKA patients. Electrolytes should be investigated and managed timely to avoid unwanted outcomes among patients admitted with DKA. Keywords: Complications, diabetic ketoacidosis, diabetes mellitus, children.